Pengetahuan Dan Sikap Remaja Putri Tentang Kehamilan Usia Dini di Posyandu Remaja Hagerek Sesama, Desa Makunjung - Fransiska Boy Sili; Sri Kustiyati (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2024)
Adolescence is a transition period from child to adult. Problems that often arise as a result of physical changes, emotional changes and social changes in adolescents are free sexual behavior, early pregnancy, and contraction of sexually transmitted diseases including HIV/AIDS. Early pregnancy can have a detrimental impact, especially for adolescent girls, both physically, phychologically and socially. Phycically, teenage mothers face a higher risk of eclampsia, puerperal endometritis , and systemic infection that women aged 20 to 24 years, and babies of teenage mothers face a higher risk of low birth weight, premature birth, and severe neonatal conditions. Objective: to determine the knowledge and attitudes of adolenscent girls about early pregnancy. Method: this type of research is a case study that uses descriptive research with a total sample of 49 people. Results: the characteristics of respondents aged 14-16 years 38%, with 59% education level is high school. Most of the knowledge of adolescent girls in youth Poanyandu Hagerek Sesama 55% in the moderate category, 33% in the good category, and 12 % in the poor category. The attitude of adolescent girls in Youth Posnyandu Remaja Hagerek Sesama was 87,76% in favor of early pregnancy and attitudes of adolescent girls about early pregnancy where most adolescent girls have sufficient knowledge and supportive attitudes.